Piers the Plowman literary relations of the A and B texts - Fowler, David C. 1921- (Univ. of Washington Press, 1961)
A comparative investigation of the two best-known versions of the famous fourteenth century English alliterative poem, one written before the Peasants' Revolt and the other after and during it, probably by two different authors.
Keywords: Langland, William <1330?-1400?> -- Piers Plowman (A-text); Langland, William <1330?-1400?> -- Piers Plowman (B-text); Langland, William -- 1332-1400 -- Piers Plowman; Piers Plowman (Langland); Tekstvarianten; Textkritik